2009
DOI: 10.1002/stem.5530150706
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of radiation-induced gene responses

Abstract: Portions of this document m y be illegible in electronic image products. Images are produced from the best available original document. ABSTFUCTIn the process of identifying genes differentially expressed in cells exposed to ultraviolet CCJV) radiation; we identified a transcript having a 25-bp region that is highly conserved among a variety of species including Bacillus circuluns, pumpkin, yeast, Drosophila, mouse, and man: 5' AAGTGTTCTGCATAAGTGGCTTCC 3'. When in the 5' region (flanking region or UTR) of a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Similarly, whole body X‐ray radiation on mice pretreated with a priming dose has been reported to exhibit fewer instances of chromosomal damage that was associated with extended survival rates 19. In contrast, several studies have also demonstrated that low‐dose radiation (<0.1 Gy) can induce detrimental perturbations in normal cellular activity 20–24. For instance, Sakamoto‐Hojo et al 25 reported variations of gene expression in human leukocytes from health‐care workers from chronic exposure of low levels of IR using cDNA microarrays.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, whole body X‐ray radiation on mice pretreated with a priming dose has been reported to exhibit fewer instances of chromosomal damage that was associated with extended survival rates 19. In contrast, several studies have also demonstrated that low‐dose radiation (<0.1 Gy) can induce detrimental perturbations in normal cellular activity 20–24. For instance, Sakamoto‐Hojo et al 25 reported variations of gene expression in human leukocytes from health‐care workers from chronic exposure of low levels of IR using cDNA microarrays.…”
Section: Introductionmentioning
confidence: 99%